Transition from unemployment to employment: monitoring, indicators, comparative analysis - Arūnas Pocius; Julija Moskvina; Boguslavas Gruževskis (Lithuanian Journal of Statistics)
Indicators that reflect the transition from unemployment to employment are an important element of the monitoring systems of employment services in EU countries. Monitoring employment trends is a complex task that usually goes beyond quantitative parameters. The correct application and interpretation of the indicators is inseparable from contextual phenomena, and the use of comparative analyses at different scales, e.g. time, territory, makes it possible to increase the informativeness of this indicator.